Leukotoxic activity of Actinobacillus actinomycetemcomitans isolated from Brazilian periodontal patients - Guazeli-Amin, V. H.; Avila-Campos, M. J.; Barbosa, D. S.; Gaetti-Jardim, E.; Trevisan, W.; Itano, E. N. (Academic Press Ltd, 2000)
The leukotoxic activity of 31 Actinobacillus actinomycetemcomitans isolates from Brazilian periodontal patients [nine from Localized Juvenile Periodontitis (LJP) patients, 22 from patients with AIDS-associated Necrotizing Ulcerative Periodontitis (AIDS/NUP)], and from the reference strain A. actinomycetemcomitans ATCC43718, were analyses for their cytotoxicity on human monocytes. A cytotoxicity inhibitory assay of the isolate P35 and the reference strain ATCC 43718 with sera from ten LJP patients and ten healthy subjects was also performed and leukotoxin reactivity was evaluated with serum from rabbits immune to leukotoxin from A. actinomycetemcomitans ATCC 43718. The cytotoxicity results were not statistically different among groups of A. actinomycetemcomitans isolates from LJP and AIDS/NUP patients, but the individual analysis of each isolate showed two isolates (P24 and P35) from LJP patients with high leukotoxic activity (P<0.05). Also, a high leucotoxic inhibitory effect with LJP patients' sera compared with healthy subjects with sonic extract from isolate P35 (P<0.05) and the reactivity of rabbit antiserum to leukotoxin were observed. Both leukotoxic and non-leukotoxic activity is more frequent in PJL than AIDS/NUP patients. Even though A. actinomycetemcomitans exhibits leukotoxic activity, there is an immune response to the leucotoxin in LJP patients. (C) 2000 Academic Press.
Keywords: Actinobacillus actinomycetemcomitans; leukotoxic activity; periodontitis; neutralization; AIDS